Spectroscopic Properties of a Biologically Relevant [Fe2(μ‐O)2] Diamond Core Motif with a Short Iron‐Iron Distance. Issue 10 (25th January 2023) - Kass, Dustin; Yao, Shenglai; Krause, Konstantin B.; Corona, Teresa; Richter, Liza; Braun, Thomas; Mebs, Stefan; Haumann, Michael; Dau, Holger; Lohmiller, Thomas; Limberg, Christian; Drieß, Matthias; et al.
Abstract: Diiron cofactors in enzymes perform diverse challenging transformations. The structures of high valent intermediates (Q in methane monooxygenase and X in ribonucleotide reductase) are debated since Fe−Fe distances of 2.5–3.4 Å were attributed to "open" or "closed" cores with bridging or terminal oxido groups. We report the crystallographic and spectroscopic characterization of a Fe III 2 (μ‐O)2 complex (2 ) with tetrahedral (4C) centres and short Fe−Fe distance (2.52 Å), persisting in organic solutions. 2 shows a large Fe K‐pre‐edge intensity, which is caused by the pronounced asymmetry at the TD Fe III centres due to the short Fe−μ−O bonds. A ≈2.5 Å Fe−Fe distance is unlikely for six‐coordinate sites in Q or X, but for a Fe2 (μ‐O)2 core containing four‐coordinate (or by possible extension five‐coordinate) iron centres there may be enough flexibility to accommodate a particularly short Fe−Fe separation with intense pre‐edge transition. This finding may broaden the scope of models considered for the structure of high‐valent diiron intermediates formed upon O2 activation in biology. Abstract : A "closed‐core" Fe III 2 (μ‐O)2 complex containing diminished Fe coordination and short Fe−Fe separation is shown to reproduce the large pre‐edge intensity typically associated with the "open‐core" structure in intermediate Q of soluble methane monooxygenase. This finding may broaden the scope of structural models considered for high‐valent diiron intermediates formed upon O2 activation in biology.